EFISIENSI FAKTOR PRODUKSI SRI REJEKI (Aglaonema commutatum) DI KOTA PEKANBARU - Sesrawati Rosa; Penti Suryani; Novianti Sunarlim (Jurnal Agroteknologi, 2012)
Aglaonema is an ornamental leafy plant which has the beauty of the form, style, and color of leaves. The plant is from the Asian countries including Indonesia. Production factors affect greatly the output obtained. The production function is a relationship between the input and the output. Results of the multiple regression analysis indicated that the F calculation (8.534) was higher than F table (2.76 at α = 0.05) which rejected Ho and accepted Ha. It meant that the size of polybag, pesticides, fertilizers and planting medium as Dummy variable jointly affected the production of Aglaonema in Pekanbaru. The R2 of 0.760 indicated that 76% of the production was affected by theses independent variable and 24% was affected by other variables. The analysis of NPM ratio for the size of polybag was 0.054 which was < 1, it meant that the use of polybag was not economically efficient yet and needed to increase the size of polybag. On the other hand NPM ratio of fertilizers was 2.84 which was >1, it meant that the use of fertilizer was not efficient and needed to decrease the amount of fertilizers.